A Study of Awareness and Perception Regarding Tax Saving Options Among Salaried People - Arora, Amit Kumar; Rathi, Priya (Indian Journal of Finance, 2018)
The study attempted to know the awareness and perception regarding various tax saving options available to save tax for salaried class employees. The study was conducted to know if there was any difference in income, savings, and investment patterns on the basis of gender as well as factors which are considered before investing in a particular investment option. The study also attempted to know which tax saving investment options are generally used to save tax. Correlation analysis was done to know the relationship among savings, investments, and income and to know whether there was any difference between men and women regarding their income, savings, and investments. Descriptive statistics was also used to present the data. The study based on 266 respondents concluded that women were more inclined towards the savings and investments as compare to men. Tax saving, risk association, and returns were the factors which were found to be considered more before making investments. The study also found PPF as the most preferable investment option due to its EEE benefits and comparatively high rate of interest. Life insurance premium and tuition fees of children were the other preferable investment options. On the other hand, NPS and NSC were found as the least preferable tax saving options. Deduction under section 80D was found to be under utilization. Most of the salaried employees were of the opinion that the tax rate should be reduced and basic exemption limit should be increased.